Mechanical properties of graphene nanocomposites: A multiscale finite element prediction. (15th November 2015) - Spanos, K.N.; Georgantzinos, S.K.; Anifantis, N.K.
Abstract: This paper describes a micromechanical finite element approach for the estimation of the elastic mechanical properties of graphene reinforced composites. These composite materials consist of graphene monolayers uniformly distributed (embedded) within the matrix. According to the micromechanical theory, these properties are estimated by considering a representative volume element, in which, the reinforcement is modeled based on its atomistic microstructure while the matrix is modeled as continuum. Spring-based finite elements are used for the simulation of the discrete geometric structure and behavior of each graphene layer. The load transfer conditions between the graphene and the matrix are modeled using joint elements connecting the two materials, simulating the interfacial region. The numerical results from finite element simulations show good agreement with existing numerical values found in the open literature.